Human mediation leads to higher compliance in digital mental health: field evidence from India - Chatterjee, Chirantan; Chugunova, Marina; Ghosh, Mainak; Singhal, Abhay; Wang, Lucy Xiaolu (Frontiers in Behavioral Economics, 2023)
Addressing the treatment gap for mental health issues around the globe and the "hidden" pandemic aggravated by COVID, digital mental health apps attempt to provide help at a low cost, conveniently, and privately. We partner with one of the largest mental health apps in India to consider how users react to automating some of the routine processes to allow operating at scale. In a field study, a prompt to complete a psychological assessment was either labeled as delivered by a system or by a human mediator. If the engagement of a human mediator was highlighted, participants were 21.75% more likely to comply by following the prompt and starting the assessment.Conditional on starting the assessment, users were equally likely to complete it. Our results highlight the fact that apart from the technical feasibility of automation, behavioral responses of users need to be taken into account when deciding what processes should be automated or if human involvement should be emphasized.